Use of Innovative Pedagogical Technologies in a Digital Educational Environment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article highlights the essence of the effective use of innovative pedagogical technologies in the digital educational environment and its importance in improving the quality of education. The article discusses the effectiveness of using innovative pedagogical technologies in the educational process.